Anal High-Grade Squamous Intraepithelial Lesions in Human Immunodeficiency Virus–Infected Men: A Study of 100 Cases With Emphasis on Cytohistologic Correlation. Issue 3 (26th February 2017) - Liu, Yuxin; Wang, Xiaofei; Kalir, Tamara; Chhieng, David; Sigel, Keith; Gaisa, Michael M.
Abstract: Objectives: Anorectal cytology (ARC) is a widely used screening tool for anal cancer in human immunodeficiency virus (HIV)–infected men who have sex with men (MSM). Its diagnostic accuracy needs to be improved, especially for high-grade squamous intraepithelial lesions (HSILs). Methods: Using 100 HIV+ MSM with biopsy-proven anal HSILs, we correlated histologic/cytologic findings. Results: Upon review, HSIL cells were present in 58 cytology samples and absent in 42. Positive samples were higher in cellularity and contained transformation zones ( P  < .05). Cytology was able to predict HSILs in 36%, 48%, 68%, and 78% of patients with one, two, three, and four or more high-grade lesions. HSIL cells were identified in all cytology samples initially reported as HSILs or atypical squamous cells, cannot exclude HSIL and in 34 samples reported as low-grade squamous intraepithelial lesions or less. Notably, among this last category, 15 (44%) were keratinized-type HSILs. Conclusions: Our findings should improve the ARC detection rate for anal HSILs, helping to implement ARC as the primary screening tool for anal cancer.